Transformation of the Thai broiler industry - Chokesomritpol, Phunjasit; Naranong, Viroj; Kennedy, Adam (International Food Policy Research Institute, 2018)
The Thai broiler industry is an innovative and successful story of transformation from a traditional “backyard” production system to a fully industrialized agri-industry. It is among the first agricultural products in Thailand that developed into a modern value chain that is fully integrated and able to expand its production to keep prices in check whilst making chicken the go-to source of protein. Highlighted by its expansion into regional and global markets through trades and investments, the success of the industry is largely a result of strong and visionary business models that calculated risks yet were clear on their objectives on how to secure emerging markets. This paper describes the development of the Thai broiler industry, documenting its path and reasons behind its success. Focus is particularly placed on the Thai industry’s leader, Charoen Pokphand Group (C.P.), and its business decisions over the years that enabled the company to gain a foothold in the highly competitive international market for chicken meat.